Reconstruction of Deep Learning-Based Practices in Islamic Education: An Analytical Study of the Hadith “Naddarallahu Imra'an” and Michael Fullan’s Framework - Shintia Faradina; Muhammad Sholihin; Iqbal Kholidi (An-Nasyi'in: Jurnal Ilmu Pendidikan, 2025)
This investigation explores how the prophetic tradition (hadith) of Prophet Muhammad, "Naddarallahu Imra'an," intersects with modern deep learning methodologies within Islamic educational contexts. The selected hadith delineates a structured cognitive progression-comprising active listening, deep comprehension, memorization, and the ethical dissemination of knowledge-which functions as a cornerstone for reflective and transformative pedagogy. Utilizing a qualitative framework grounded in library research, this study examines the normative dimensions of the text, establishes a conceptual dialogue with Michael Fullan’s deep learning paradigm, and synthesizes contemporary literature on digital instructional innovations and meaningful learning. The findings indicate that modern deep learning principles-specifically the cultivation of critical thinking, collaboration, creativity, communication, and character-strongly resonate with classical Islamic tenets such as trustworthiness (amanah), moral integrity, and the internal processing of knowledge. This synthesis highlights that contemporary Islamic schooling can successfully incorporate digital tools and modern pedagogical strategies while preserving its core spiritual values and academic ethics. Furthermore, the study underscores the necessity of redefining the educator's role into that of a facilitator who fosters student agency, active participation, and the contextual transfer of knowledge. Consequently, an Islamic instructional model rooted in deep learning offers an adaptable, transformative, and practical framework designed to prepare students for the global and technological demands of the 21st century. This research provides both theoretical insights and practical guidance for contemporary Islamic educational strategies, bridging prophetic values with modern competencies.